An automated fire fighting system - Shams, Rafat; Hossain, Shafkat; Priyom, Shaoni; Fatema, Nusrat; Shakil, Shifur Rahman; Rhaman, Md. Khalilur (© 2015 IEEE, 2016)
This conference paper was presented in the 12th International Conference on Fuzzy Systems and Knowledge Discovery, FSKD 2015; Zhangjiajie; China; 15 August 2015 through 17 August 2015 [© 2015 IEEE] The conference paper's definite version is available at: http://dx.doi.org/10.1109/FSKD.2015.7382316